The unique history of a trickster Riffian and a clever General: Manuel Galbán Jiménez and his Disaster of Annual (1921) - Gajate Bajo, María (Hispania Nova, 2021)
Manuel Galbán was a columnist from Melilla closely linked to El Telegrama del Rif. Working from administrator to director, he knew the ins and outs of this periodical publication as far as he witnessed all the military campaigns in Morocco and, in 1965, after a long digestion, published España en África. La pacificación de Marruecos. His testimony, which combines a firsthand experience with his mature judgment, has not received excessive historiographical attention. Despite this fact, the comments made on the military campaign of 1909, concerning certain legal aspects of the Protectorate, related to the businesses of Abd-el-Krim, the relationship between Berenguer and Silvestre or to the motivations of Juan Picasso, stand out for their uniqueness and are particularly relevant when it meets the first centenary of the Disaster of Annual and the Primo de Rivera’s coup d’etat. In short, this gigantic military setback greatly contributed to the definition of the Africanist caste as well as to the incubation of the military coup of 1923.
Keywords: Manuel Galbán Jiménez; Annual; africanism; Riffian mines; responsibilities